Preoccupations and Prejudices: Reflections on the Study of Sports Imagery - King, C. Richard (Anthropologica, 2022)
This essay examines the predicaments and possibilities of the anthropological study of sport, arguing that it offers anthropologists unique opportunities to fashion engaged, critical, and public anthropologies. It focusses on sports mascots and how they epitomize the promise of the anthropological study of sports. It begins with a consideration of the disciplinary biases and barriers that have prevented anthropologists from taking the study of sports seriously. Against this background, it reviews a number of ongoing struggles over racialized imagery in sports, highlighting their relevance for the formulation of engaged anthropologies.